Immunohistochemical characterization of stem cell and differentiation markers of the dental pulp of human natal teeth. (4th October 2018) - Shetty, Heeresh; Kakade, Adesh; Shetty, Shishir; Neelakantan, Prasanna; Nagar, Saurabh; Desai, Rajiv S; Beri, Kavita
Aim: Dental pulp stem cells, which are primarily derived from the pulp tissues of human teeth, have rarely been obtained from natal teeth. This study investigated the stem cell and differentiation markers of the dental pulp of natal teeth using immunohistochemistry.Materials & methods: The pulp tissue from extracted natal teeth (n = 2) of a 20-day-old healthy male was examined for immunohistochemical expression of stem cell (Oct-4 and SOX 2) and differentiation markers (Nestin, CD 44, desmin, osteopontin and Ki- 67).Results: The pulp tissue of the natal teeth expressed immunopositivity for nestin, CD 44 and SOX2.Conclusion: Natal teeth, if preserved properly, could serve as sources of dental pulp stem cells that are an improvement on deciduous teeth. Lay abstract: Natal teeth are present at birth. They are usually removed prophylactically to avoid the complications such as aspiration, ulcerations on the tongue and injuries to the mother during feeding. To study discarded natal teeth as a potential stem cell source, immunohistochemistry was used to check for the expression of stem cells and markers on the dental pulp of the natal teeth. This was compared with the stem cell potential of deciduous teeth. Natal teeth exhibited higher immunohistochemical expression, which suggests that discarded tissues like natal teeth are a potential source for stem cells.